2015
DOI: 10.1097/yct.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Ketamine Combined With Propofol on Phosphorylation of AMPA Receptor GluR1 Subunit and GABAA Receptor in Hippocampus of Stressed Rats Receiving Electroconvulsive Shock

Abstract: Low-dose ketamine combined with propofol may play a role in enhancing the antidepressant efficacy of ECS in stressed rats, ameliorating the cognitive impairment associated with ECS by balancing the expression of p-GluR1 and p-GABAAR in the hippocampus of stressed rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The CUMS procedure, which has been successfully used in previous studies to establish animal models of depression (17,29,37), was first successfully established by Willner et al (38) in 1987. However, it should be noted that CUMS procedures may differ slightly in certain aspects between different laboratories, primarily due to convenience and logistics (29,39).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The CUMS procedure, which has been successfully used in previous studies to establish animal models of depression (17,29,37), was first successfully established by Willner et al (38) in 1987. However, it should be noted that CUMS procedures may differ slightly in certain aspects between different laboratories, primarily due to convenience and logistics (29,39).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous results, a constant dosage of anesthetics, ketamine (10 mg/kg) and propofol (80 mg/kg), was administered intraperitoneally (i.p.) 10 min prior to ECS treatment in each group (17). On the day of the experiment, the rats were anesthetized to prepare them for MECS treatments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In stressed rats undergoing ECT, ketofol played an important role in enhancing antidepressant efficacy and ameliorating neurocognitive impairment. 5 Wang et al found that ketofol was superior in improving depressive symptoms over propofol alone and was associated with fewer adverse events than ketamine alone, suggesting that ketofol should be considered as the firstchoice anaesthesia in patients with MDD undergoing ECT. 3 The neurobiological mechanisms underlying the antidepressant effects of ketofol anaesthesia in ECT are complex and not fully understood.…”
Section: Introductionmentioning
confidence: 99%